Analysis of the Relation Between Screen Time and Sleep Quality with Iron Deficiency Anemia in Class X Girls at SHS 1 Dukun - Maulidani Rahman Putra, Rizky Dwi; Mulyani, Endah (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Iron-deficiency anemia poses a significant health concern, particularly among adolescent girls, as it can adversely affect concentration and academic performance. According to the 2024 World Health Organization (WHO) guidelines, a hemoglobin level above 12 g/dL is considered normal for individuals aged 15–24 years. Objective: This study aimed to investigate the relationship between screen time duration and sleep quality with the incidence of iron-deficiency anemia among grade X female students at SHS 1 Dukun. Method: A quantitative, analytical observational method with a cross-sectional design was employed. A total of 60 participants were selected through random sampling using the Slovin formula. Chi-square tests and odds ratios (OR) were used for statistical analysis. Results showed that 28 students (46.6%) had iron-deficiency anemia, while 32 (53.4%) did not. Result and Discussion: The analysis found no significant association between screen time duration and anemia. Conclusion: However, a significant relationship was found between sleep quality and anemia, with a p-value of 0.003 and an OR of 14.